2020
DOI: 10.34050/els-jish.v3i1.9524
|View full text |Cite
|
Sign up to set email alerts
|

Native English Teacher’s Politeness Realizations in EFL Classroom Interaction

Abstract: The realizations of politeness need to be implemented in the process of teaching and learning in the class, especially in English language classroom context. Applying appropriate politeness strategy in talking to the students is very important to create effective teaching and learning process. This study examines politeness strategies used by the native English teacher. It aims to identify the use of politeness strategies realized by the native English teacher in classroom interaction. This research was qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…From 7 zoom classes consists 137 students dominated positive politeness strategy. Compared to learning process in face to face interaction, this study supports the previous presented studies by (Nurmawati, Atmowardono & Weda (2019); Nugrahanto & Hartono (2019); Rahayuningsih (2019), Heriyawati, Siba & Sulistyo (2019); Fitryani (2020), and Wijayanti, Wijayanto & Marmanto (2020) which proved the existing of applying the four types of politeness strategies which is positive politeness strategies dominantly used could create the effective interaction between teacher and students In addition, in formal contexts apply the three variables of politeness, namely : Power (P) which refers to social status, Distance (D) which refers to the level of closeness of the speech participants, and Kinship (K) which refers to the level of kinship as stated by Yassi in Novalia et al, (2020). In the comments above, students used only two varibales, namely: Power (P) and Kinship (K).…”
Section: Discussionsupporting
confidence: 90%
“…From 7 zoom classes consists 137 students dominated positive politeness strategy. Compared to learning process in face to face interaction, this study supports the previous presented studies by (Nurmawati, Atmowardono & Weda (2019); Nugrahanto & Hartono (2019); Rahayuningsih (2019), Heriyawati, Siba & Sulistyo (2019); Fitryani (2020), and Wijayanti, Wijayanto & Marmanto (2020) which proved the existing of applying the four types of politeness strategies which is positive politeness strategies dominantly used could create the effective interaction between teacher and students In addition, in formal contexts apply the three variables of politeness, namely : Power (P) which refers to social status, Distance (D) which refers to the level of closeness of the speech participants, and Kinship (K) which refers to the level of kinship as stated by Yassi in Novalia et al, (2020). In the comments above, students used only two varibales, namely: Power (P) and Kinship (K).…”
Section: Discussionsupporting
confidence: 90%
“…Soviana Mukminatien (2020) studied politeness strategies and illocutionary acts. Meanwhile, Wijayanti et al (2020) elaborated politeness realisation by native English teachers. Different from the other studies, Yrisarry et al (2019) attempted to utilise politeness strategies to the students' uncivil behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The communication in teaching is not only to transfer knowledge but also to create a comfortable atmosphere that can create solidarity and cooperation with the use of expressions such as greetings, gratitude and apology (Astuti 2017;Andi, 2018;Widana, 2018;Mahmud, 2019). In addition, Nurmawati, Atmowardoyo & Weda (2019), Nugrahanto & Hartono (2019), Rahayuningsih (2019), Heriyawati, Siba & Sulistyo (2019), Fitryani (2020) and Wijayanti, Wijayanto & Marmanto (2020) proved the existing of the four types of politeness strategies and the dominant use of positive politeness strategies in the classroom interaction created effective interaction not only between teacher and students but also among the student body. Aside from greetings, gratitude, apology, Yusuf & Anwar (2019) also found that English students apply vernacular language to soften their language during class presentations' discussions.…”
Section: Introductionmentioning
confidence: 99%